Pannexin channels mediate the acquisition of myogenic commitment in C2C12 reserve cells promoted by P2 receptor activation - Riquelme, Manuel A.; Cea, Luis A.; Vega, José L.; Puebla, Carlos; Vargas, Aníbal A.; Shoji, Kenji F.; Subiabre, Mario; Sáez, Juan C. (Frontiers in Cell and Developmental Biology, 2015)
The acquisition of myoblast commitment to the myogenic linage requires rises in intracellular free Ca2+ concentration ([Ca2+]i). Putative cell membrane pathways involved in these [Ca2+]i increments are P2 receptors (P2Rs) as well as connexin (Cx) and/or pannexin (Panx) hemichannels and channels (Cx HChs and Panx Chs), respectively, which are known to permeate Ca2+. Reserve cells (RCs) are uncommitted myoblasts obtained from differentiated C2C12 cell cultures, which acquire commitment upon replating. Regarding these cells, we found that extracellular ATP increases the [Ca2+]i via P2Rs. Moreover, ATP increases the plasma membrane permeability to small molecules and a non-selective membrane current, both of which were inhibited by Cx HCh/Panx1Ch blockers. However, RCs exposed to divalent cation-free saline solution, which is known to activate Cx HChs (but not Panx Chs), did not enhance membrane permeability, thus ruling out the possible involvement of Cx HChs. Moreover, ATP-induced membrane permeability was inhibited with blockers of P2Rs that activate Panx Chs. In addition, exogenous ATP induced the expression of myogenic commitment and increased MyoD levels, which was prevented by the inhibition of P2Rs or knockdown of Panx1 Chs. Similarly, increases in MyoD levels induced by ATP released by RCs were inhibited by Panx Ch/Cx HCh blockers. Myogenic commitment acquisition thus requires a feed-forward mechanism mediated by extracellular ATP, P2Rs and Panx Chs.